The Impact of ESG (Environmental, Social And Governance) Implementation on Financial Performance in Mining Companies - Nurrahmaniah Nurrahmaniah; Popong Nurhayati; Bagus Sartono (Dinasti Publisher, 2025)
The mining industry plays an essential role in the national economy, but it also has severe environmental impacts. Therefore, Corporate Sustainability Disclosure (CSD) is needed to ensure transparent, accountable reporting on sustainability risk mitigation and the improvement of companies' Environmental, Social, and Governance (ESG) practices. This study aims to analyze the effect of ESG disclosure transparency on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2023. This study uses secondary data from annual, financial, and sustainability reports from the IDX and from companies' financial reports. The research sample comprises 40 companies selected through purposive sampling. This study uses panel data regression analysis with the Fixed-Effects and Random-Effects models selected via the Hausman test. The results of this study indicate that the level of sustainability disclosure and ESG scores of mining companies have increased consistently since 2020. The analysis results indicate that ESG disclosure has a positive and significant effect on ROA and ROE, suggesting that ESG transparency can enhance operational efficiency, strengthen risk management, and increase investor confidence.